PATHOGENICITY TEST OF VARIOUS CONCENTRATIONS OF Beauveria bassiana CULTURED ON RICE BRAN AND CORN MEDIA AGAINST COFFEE FRUITS BORER (Hyphotenemus hampei) - Chimayatus Solichah; Anindita Widyaningtyas; Rukmowati Brotodjojo (UNIVERSITAS PEMBANGUNAN NASIONAL ”VETERAN” YOGYAKARTA, 2019)
Coffee is a commodity with high value for export. Coffee bean borer (Hypothenemus hampei) is the main pest causing the decline in coffee production. Farmers still rely on chemical insecticides to control this pest. To reduce the negative impact of insecticides, entomopathogen Beauveria bassiana is applied. The research aimed to investigating the level of pathogenicity of B. bassiana in controlling H. hampei, and investigating the concentration with the highest level of pathogenicity of B. Bassiana against H. hampei. Laboratory research was arranged in one factor Completely Random Design (CRD). This research used 8 (eight) treatments namely KO: Aquades, Kk: Lamda Sihalothrin 25 EC (Chemical Insecticide), B1: 10 g / L B. bassiana cultivated in rice bran media, B2: 20 g / L B. bassiana cultivated in rice bran media, B3: 30 g / L B. bassiana cultivated in rice bran media, B4: 10 g / L B. bassiana grown on corn media, B5: 20 gL B. bassiana grown on corn and B6: 30 g / L B. bassiana grown on corn media. Each treatment used coffee beans infested with 20 H. hampei and repeated 4 (four) times. The result of the research showed that B. bassiana was able to kill H. hampei. The concentration that was able to cause the fastest mortality with a high level of pathogenicity based on the pathogenicity test of B. bassiana on H. hampei (percentage of mortality, total mortality time, and feeding capacity) was 30 g/L of B. bassiana cultivated in rice bran media.Key words: Beauveria bassiana, Hypothenemus hampei, chemical insecticide, coffee bean